2016
DOI: 10.1186/s13287-016-0427-8
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1-transduced bone marrow mesenchymal stem cells in reducing acute rejection and improving small bowel transplantation outcomes in rats

Abstract: BackgroundWe determined whether bone marrow mesenchymal stem cells (BMMSCs) transduced with heme oxygenase-1 (HO-1), a cytoprotective and immune-protective factor, could improve outcomes for small bowel transplantation (SBTx) in rats.MethodsWe performed heterotopic SBTx from Brown Norway rats to Lewis rats, before infusing Ad/HO-1-transduced BMMSCs (Ad/HO-1/BMMSCs) through the superficial dorsal veins of the penis. Respective infusions with Ad/BMMSCs, BMMSCs, and normal saline served as controls. The animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 71 publications
4
29
0
Order By: Relevance
“…Isolation, culture, and characterization of BMMSCs were performed according to previously described methods [24,27]. Briefly, BMMSCs were isolated from the femur and tibia of male SD rats and cultured in a cell culture incubator.…”
Section: Preparation and Identification Of Ho-1/bmmscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation, culture, and characterization of BMMSCs were performed according to previously described methods [24,27]. Briefly, BMMSCs were isolated from the femur and tibia of male SD rats and cultured in a cell culture incubator.…”
Section: Preparation and Identification Of Ho-1/bmmscsmentioning
confidence: 99%
“…However, BMMSC therapy has the disadvantage of insufficient migration to target organs and short survival time. Heme oxygenase 1 (HO-1), a potent cytoprotective enzyme, has been shown to exhibit antioxidant and antiapoptotic properties, reduce cell damage, regulate immunity, and prolong the survival time of BMMSCs and enhance their activity [24][25][26]. In this study, HO-1modified BMMSCs (HO-1/BMMSCs) were perfused into DCD liver grafts by NMP to increase the amount of BMMSCs in the target organ, thus enhancing their protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is now evident that epithelial apoptosis is the mechanism of cell death in allograft rejection. [ 24 ] In the present study, less extensive cell apoptosis was found in the allograft after autologous ADSCs transplantation. Du et al .…”
Section: Discussionsupporting
confidence: 44%
“…The HITx has been used to establish the proof of concept of different immune modulation strategies to avoid rejection, as well as to study immunological reactions involved in graft rejection. 6 - 10 …”
mentioning
confidence: 99%